On Anthyllis onobrychioides Cav. and the genus Dorycnopsis Boiss. (Leguminosae-Loteae) - Ginés López González (Anales del Jardín Botánico de Madrid)
Anthyllis onobrychioides and Anthyllis gerardi are two closely related species included by De Candolle in an individual section, Anthyllis sect. Dorycnioides, the second being the type of the monotypic genus Dorycnopsis Boiss. A morphological study of both species shows that the characters on which the genus Dorycnopsis is based are not consistent, and Dorycnopsis is here included in Anthyllis L. Anthyllis sect. Dorycnioides DC. is lectotypified with A. onobrychioides Cav.